REVIEW OF ONE HUNDRED CONSECUTIVE ABDOMINAL HYSTERECTOMIES: THEIR SUITABILITY FOR VAGINAL HYSTERECTOMY - Malik, Nafeesa (Journal of Ayub Medical College Abbottabad, 2015)
Background: Abdominal hysterectomy is one of the most common major operations in gynaecology. However, it is associated with considerable morbidity and relatively slow recovery. The superiority of hysterectomy by the vaginal route is not denied. It is associated with a significant fewer complications than abdominal hysterectomy. This study was done with the aim to determine what proportion of hysterectomies performed via abdominal route could have been performed vaginally or with laparoscopic assistance. Methods: Case notes of one hundred consecutive patients who had an abdominal hysterectomy were obtained from the records department. Out of 100 cases only 85 case notes were made available for analysis. Results: A total of 74 cases for benign disorder were studied; 50% of the cases were over the age of 40 years and 82% of the patients were multiparous. The uterine size was less than 12 weeks in 67 cases. About 44.6% of cases were found to have menorrhagia without any organic pathology. For the majority of cases it was not apparent from the cases notes as to the degree of uterine descent. Three patients required blood transfusion in the preoperative group and 7 cases in the postoperative group. Primary haemorrhage was noted in 3 cases. Three patients needed readmission for secondary haemorrhage due to vault hematoma formation and in one case a hematoma of rectus sheath was noted which needed drainage. Paralytic ileus was noted in 2 cases and one case had intestinal obstruction. Most of the patients were allowed home within 7 days. One patient stayed for 17 days due to intestinal obstruction requiring laparotomies and gut resection. Majority of the cases were done by the consultants. Conclusion: By considering the specific guidelines for vaginal hysterectomy, every patient who need hysterectomy should be assessed for vaginal hysterectomy, provided there is no contraindication for it. Preoperative assessment under anaesthesia should be an integral part of management of a patient needing hysterectomy. Keywords: Abdominal hysterectomy, vaginal hysterectomy, Menorrhagia, Dysfunctional uterine bleeding